Skip to main content
\(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\)
Mathematics LibreTexts

Section 11.3 Answers

  • Page ID
    30074
  • \( \newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} } \) \( \newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}} \)\(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\) \(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\)

    1. \(C(x)=\frac{L^{2}}{3}+\frac{4L^{2}}{\pi ^{2}}\sum_{n=1}^{\infty}\frac{(-1)^{n}}{n^{2}}\cos\frac{n\pi x}{L}\)

    2. \(C(x)=\frac{1}{2}+\frac{4}{\pi ^{2}}\sum_{n=1}^{\infty}\frac{1}{(2n-1)^{2}}\cos (2n-1)\pi x\)

    3. \(C(x)=-\frac{2L^{2}}{3}+\frac{4L^{2}}{\pi ^{2}}\sum_{n=1}^{\infty}\frac{1}{n^{2}}\cos\frac{n\pi x}{L}\)

    4. \(C(x)=\frac{1-\cos k\pi}{k\pi}-\frac{2k}{\pi}\sum_{n=1}^{\infty}\frac{[1-(-1)^{n}\cos k\pi}{n^{2}-k^{2}}\cos nx\)

    5. \(C(x)=\frac{1}{2}-\frac{2}{\pi}\sum_{n=1}^{\infty}\frac{(-1)^{n}}{2n-1}\cos\frac{(2n-1)\pi x}{L}\)

    6. \(C(x)=-\frac{2L^{2}}{3}+\frac{4L^{2}}{\pi ^{2}}\sum_{n=1}^{\infty}\frac{(-1)^{n}}{n^{2}}\cos\frac{n\pi x}{L}\)

    7. \(C(x)=\frac{1}{3}+\frac{4}{\pi ^{2}}\sum_{n=1}^{\infty}\frac{1}{n^{2}}\cos n\pi x\)

    8. \(C(x)=\frac{e^{\pi}-1}{\pi }+\frac{2}{\pi}\sum_{n=1}^{\infty}\frac{[(-1)^{n}e^{\pi}-1]}{(n^{2}+1)}\cos nx\)

    9. \(C(x)=\frac{L^{2}}{6}-\frac{L^{2}}{\pi ^{2}}\sum_{n=1}^{\infty}\frac{1}{n^{2}}\cos\frac{2n\pi x}{L}\)

    10. \(C(x)=-\frac{2L^{2}}{3}+\frac{4L^{2}}{\pi ^{2}} \sum_{n=1}^{\infty}\frac{1}{n^{2}}\cos\frac{n\pi x}{L}\)

    11. \(S(x)=\frac{4}{\pi} \sum_{n=1}^{\infty}\frac{1}{(2n-1)}\sin\frac{(2n-1)\pi x}{L}\)

    12. \(S(x)=\frac{2}{\pi} \sum_{n=1}^{\infty}\frac{1}{n}\sin n\pi x\)

    13. \(S(x)=\frac{2}{\pi} \sum_{n=1}^{\infty}[1-(-1)^{n}\cos k\pi]\frac{n}{n^{2}-k^{2}}\sin nx\)

    14. \(S(x)=\frac{2}{\pi} \sum_{n=1}^{\infty}\frac{1}{n}\left[1-\cos\frac{n\pi}{2}\right]\sin\frac{n\pi x}{L}\)

    15. \(S(x)=\frac{4L}{\pi ^{2}} \sum_{n=1}^{\infty}\frac{(-1)^{n+1}}{(2n-1)^{2}}\sin\frac{(2n-1)\pi x}{L}\)

    16. \(S(x)=\frac{\pi}{2}\sin x-\frac{16}{\pi} \sum_{n=1}^{\infty}\frac{n}{(4n^{2}-1)^{2}}\sin 2nx\)

    17. \(S(x)=-\frac{2}{\pi} \sum_{n=1}^{\infty}\frac{n[(-1)^{n}e^{\pi}-1]}{(n^{2}+1)}\sin nx\)

    18. \(C_{M}(x)=-\frac{4}{\pi} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{2n-1}\cos\frac{(2n-1)\pi x}{2L}\)

    19. \(C_{M}(x)=-\frac{4L^{2}}{\pi} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{2n-1}\left[1-\frac{8}{(2n-1)^{2}\pi ^{2}}\right]\cos\frac{(2n-1)\pi x}{2L}\)

    20. \(C_{M}(x)=-\frac{4}{\pi} \sum_{n=1}^{\infty}\left[ (-1)^{n}+\frac{2}{(2n-1)\pi}\right]\cos\frac{(2n-1)\pi x}{2}\)

    21. \(C_{M}(x)=-\frac{4}{\pi} \sum_{n=1}^{\infty}\frac{1}{2n-1}\cos\frac{(2n+1)\pi}{4}\cos\frac{(2n-1)\pi x}{2L}\)

    22. \(C_{M}(x)=\frac{4}{\pi} \sum_{n=1}^{\infty}(-1)^{n}\frac{2n-1}{(2n-3)(2n+1)}\cos\frac{(2n-1)x}{2}\)

    23. \(C_{M}(x)=-\frac{8}{\pi} \sum_{n=1}^{\infty}\frac{1}{(2n-3)(2n+1)}\cos\frac{(2n-1)x}{2}\)

    24. \(C_{M}(x)=-\frac{8L^{2}}{\pi ^{2}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{2}}\left[1+\frac{4(-1)^{n}}{(2n-1)\pi}\right]\cos\frac{(2n-1)\pi x}{2L}\)

    25. \(S_{M}(x)=\frac{4}{\pi} \sum_{n=1}^{\infty}\frac{1}{(2n-1)}\sin\frac{(2n-1)\pi x}{2L}\)

    26. \(S_{M}(x)=-\frac{16L^{2}}{\pi ^{2}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{2}}\left[ (-1)^{n}+\frac{2}{(2n-1)\pi}\right]\sin\frac{(2n-1)\pi x}{2L}\)

    27. \(S_{M}(x)=\frac{4}{\pi} \sum_{n=1}^{\infty}\frac{1}{2n-1}\left[ 1-\cos\frac{(2n-1)\pi }{4}\right]\sin\frac{(2n-1)\pi x}{2L}\)

    28. \(S_{M}(x)=\frac{4}{\pi} \sum_{n=1}^{\infty}\frac{2n-1}{(2n-3)(2n+1)}\sin\frac{(2n-1)x}{2}\)

    29. \(S_{M}(x)=\frac{8}{\pi} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{(2n-3)(2n+1)}\sin\frac{(2n-1)x}{2}\)

    30. \(S_{M}(x)=\frac{8L^{2}}{\pi ^{2}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{2}}\left[(-1)^{n}+\frac{4}{(2n-1)\pi}\right]\sin\frac{(2n-1)\pi x}{2L}\)

    31. \(C(x)=-\frac{7L^{4}}{5}-\frac{144L^{4}}{\pi ^{4}} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{n^{4}}\cos\frac{n\pi x}{L}\)

    32. \(C(x)=-\frac{2L^{4}}{5}-\frac{48L^{4}}{\pi ^{4}} \sum_{n=1}^{\infty}\frac{1+(-1)^{n}2}{n^{4}}\cos\frac{n\pi x}{L}\)

    33. \(C(x)=\frac{3L^{4}}{5}-\frac{48L^{4}}{\pi ^{4}} \sum_{n=1}^{\infty}\frac{2+(-1)^{n}}{n^{4}}\cos\frac{n\pi x}{L}\)

    34. \(C(x)=\frac{L^{4}}{30}-\frac{3L^{4}}{\pi ^{4}} \sum_{n=1}^{\infty}\frac{1}{n^{4}}\cos\frac{2n\pi x}{L}\)

    36. \(S(x)=\frac{8L^{2}}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\sin\frac{(2n-1)\pi x}{L}\)

    37. \(S(x)=-\frac{4L^{3}}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{(1+(-1)^{n}2)}{n^{3}}\sin\frac{n\pi x}{L}\)

    38. \(S(x)=-\frac{12L^{3}}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{n^{3}}\sin\frac{n\pi x}{L}\)

    39. \(S(x)=\frac{96L^{4}}{\pi ^{5}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{5}}\sin\frac{(2n-1)\pi x}{L}\)

    40. \(S(x)=-\frac{720L^{5}}{\pi ^{5}} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{n^{5}}\sin\frac{n\pi x}{L}\)

    41. \(S(x)=-\frac{240L^{5}}{\pi ^{5}} \sum_{n=1}^{\infty}\frac{1+(-1)^{n}2}{n^{5}}\sin\frac{n\pi x}{L}\)

    43. \(C_{M}(x)=-\frac{64L^{3}}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\left[(-1)^{n}+\frac{3}{(2n-1)\pi}\right]\cos\frac{(2n-1)\pi x}{2L}\)

    44. \(C_{M}(x)=-\frac{32L^{2}}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{(2n-1)^{3}}\cos\frac{(2n-1)\pi x}{2L}\)

    45. \(C_{M}(x)=-\frac{96L^{3}}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\left[(-1)^{n}+\frac{2}{(2n-1)\pi}\right]\cos\frac{(2n-1)\pi x}{2L}\)

    46. \(C_{M}(x)=\frac{96L^{3}}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\left[(-1)^{n}3+\frac{4}{(2n-1)\pi}\right]\cos\frac{(2n-1)\pi x}{2L}\)

    47. \(C_{M}(x)=\frac{96L^{3}}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\left[(-1)^{n}5+\frac{8}{(2n-1)\pi}\right]\cos\frac{(2n-1)\pi x}{2L}\)

    48. \(C_{M}(x)=-\frac{384L^{4}}{\pi ^{4}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{4}}\left[1+\frac{(-1)^{n}4}{(2n-1)\pi}\right]\cos\frac{(2n-1)\pi x}{2L}\)

    49. \(C_{M}(x)=-\frac{768L^{4}}{\pi ^{4}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{4}}\left[ 1+\frac{(-1)^{n}2}{(2n-1)\pi}\right]\cos\frac{(2n-1)\pi x}{2L}\)

    51. \(S_{M}(x)=\frac{32L^{2}}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\sin\frac{(2n-1)\pi x}{2L}\)

    52. \(S_{M}(x)=-\frac{96L^{3}}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\left[1+(-1)^{n}\frac{4}{(2n-1)\pi}\right]\sin\frac{(2n-1)\pi x}{2L}\)

    53. \(S_{M}(x)=\frac{96L^{3}}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\left[1+(-1)^{n}\frac{2}{(2n-1)\pi}\right]\sin\frac{(2n-1)\pi x}{2L}\)

    54. \(S_{M}(x)=\frac{192L^{3}}{\pi ^{4}}\sum_{n=1}^{\infty}\frac{(-1)^{n}}{(2n-1)^{4}}\sin\frac{(2n-1)\pi x}{2L}\)

    55. \(S_{M}(x)=\frac{1536L^{4}}{\pi ^{4}}\sum_{n=1}^{\infty}\frac{1}{(2n-1)^{4}}\left[(-1)^{n}+\frac{3}{(2n-1)\pi}\right]\sin\frac{(2n-1)\pi x}{2L}\)

    56. \(S_{M}(x)=\frac{384L^{4}}{\pi ^{4}}\sum_{n=1}^{\infty}\frac{1}{(2n-1)^{4}}\left[ (-1)^{n}+\frac{4}{(2n-1)\pi}\right]\sin\frac{(2n-1)\pi x}{2L}\)